Transplantation of Human Neural Progenitor Cells (NPC) into Putamina of Parkinsonian Patients: A Case Series Study, Safety and Efficacy Four Years after Surgery. Issue 3 (March 2019) - Madrazo, I.; Kopyov, O.; Ávila-Rodríguez, M. A.; Ostrosky, F.; Carrasco, H.; Kopyov, A.; Avendaño-Estrada, A.; Jiménez, F.; Magallón, E.; Zamorano, C.; González, G.; Valenzuela, T.; et al.
Individuals with Parkinson's disease (PD) suffer from motor and mental disturbances due to degeneration of dopaminergic and non-dopaminergic neuronal systems. Although they provide temporary symptom relief, current treatments fail to control motor and non-motor alterations or to arrest disease progression. Aiming to explore safety and possible motor and neuropsychological benefits of a novel strategy to improve the PD condition, a case series study was designed for brain grafting of human neural progenitor cells (NPCs) to a group of eight patients with moderate PD. A NPC line, expressing Oct-4 and Sox-2, was manufactured and characterized. Using stereotactic surgery, NPC suspensions were bilaterally injected into patients' dorsal putamina. Cyclosporine A was given for 10 days prior to surgery and continued for 1 month thereafter. Neurological, neuropsychological, and brain imaging evaluations were performed pre-operatively, 1, 2, and 4 years post-surgery. Seven of eight patients have completed 4-year follow-up. The procedure proved to be safe, with no immune responses against the transplant, and no adverse effects. One year after cell grafting, all but one of the seven patients completing the study showed various degrees of motor improvement, and five of them showed better response to medication. PET imaging showed a trend toward enhanced midbrain dopaminergic activity. By their 4-year evaluation, improvements somewhat decreased but remained better than at baseline. Neuropsychological changes were minor, if at all. The intervention appears to be safe. At 4 years post-transplantation we report that undifferentiated NPCs can be delivered safely by stereotaxis to both putamina of patients with PD without causing adverse effects. In 6/7 patients in OFF condition improvement in UPDRS III was observed. PET functional scans suggest enhanced putaminal dopaminergic neurotransmission that could correlate with improved motor function, and better response to L-DOPA. Patients' neuropsychological scores were unaffected by grafting. Trial Registration: Fetal derived stem cells for Parkinson's diseasehttps://doi.org/10.1186/ISRCTN39104513Reg#ISRCTN39104513